428 - DEMENTIA INPATIENT THERAPEUTIC INTERVENTIONS IN A SCOTTISH HEALTH REGION. (October 2020) - Stevenson, Gary; Foster, Stephen; Grove, Meroe
Abstract : Background: There is published evidence of the benefits and limitations, including potential harm, of psychotropic medication and benefits of non-pharmacological interventions for the management of challenging behaviours associated with dementia (BPSD). Objectives: To examine the usage of such interventions in the management of BPSD within three National Health Service (NHS) 'specialist' dementia inpatient wards (56 beds) in a Scottish health region (Fife, population 370, 000) and to identify targets for service improvements. Methods: Patient demographic data, mental and physical health diagnoses, current and recent (within 3 months) psychotropic prescriptions, multidisciplinary team input, and evidence of individualised non-pharmacological interventions for BPSD were collected in February 2020 from patient notes, care plans and medication charts. Results: 42 older patients (mean age 80 years, range 59-99) with dementia had spent on average 18.7 months within hospital, some categorised as 'delayed discharges' awaiting care home placements All lacked capacity to consent to their general care and medical treatments, most having multiple (average 5) medical co-morbidities. 36% were detained in hospital under Mental Health legislation, 29% prescribed medications so authorised, and 40% had medications administered covertly. 76% were prescribed an antipsychotic (Risperidone in 24%), 40% a cognitive enhancer (Memantine and/or a cholinesterase inhibitor), 48% an antidepressant (Trazodone in 19%), 26% a regular benzodiazepine. There was limited regular multi-professional team working in the wards (under 18% had any non-nursing input within the previous 3 months). Of non-pharmacological therapeutic interventions, 26% were receiving multisensory inputs, 19% soft toy, 12% massage, 7% music playlist and 7% cognitive stimulation therapy. Conclusions: For this population with BPSD there were high rates of off -licence drug prescribing with limited investment in evidence-based non-pharmacological therapeutic alternatives. During ongoing review of staffing on these wards, it would appear appropriate to examine the expectation that wards serve multiple functions, such as transitional care and specialist continuing care. We suggest reviews contextualise prescribing within an increased availability of multi-disciplinary therapeutic interventions, to ensure this patient population is cared for in an evidence-based therapeutic environment. The Scottish Government's publication 3 (2018) " Transforming Specialist Dementia Hospital Care " should help raise the profile of this "overlooked" inpatient population. 3 https://www.gov.scot/publications/transforming-specialist-dementia-hospital-care/